DECONSTRUCTING SIMPLE EVIDENCE IN BANKRUPTCY PETITION FOR LEGAL CERTAINTY - Shubhan, M. Hadi (Indonesia Law Review, 2019)
This study analyzed the theories, norms, and practice of simple evidence (pembuktian sederhana) which have become the requirements for bankruptcy petition applications. The evidence applied in the procedure law of the bankruptcy petition and the Suspension of Debt Repayment Obligation or PKPU was simple evidence. The existence of the simple evidence requirement actually caused the bankruptcy petition to have a complication and legal uncertainty. Therefore, the norm of simple evidence needs to be reconstructed. The aspects that have fulfilled simple evidence in the bankruptcy petition or PKPU application included two (2) bankruptcy requirements, namely, unpaid debt that has matured and is collectible and the presence of at least two creditors. The research results found that the Bankruptcy Law determined that simple evidence in bankruptcy was necessary. However, the Bankruptcy Law did not definitively set the limits referred to as simple evidence, which resulted in norm obscurity. In practice, the judges had rejected bankruptcy petitions with unimportant considerations in evidence. In addition, disparities took place in bankruptcy decisions in applying simple evidence because there were complicated cases regarding the conditions for bankruptcy petitions. The court, on the other hand, considered and decided that the cases were not simple. Conversely, there were also simple cases that were adjudicated by the court to be not simple, thus, their bankruptcy petitions were overruled.